Protocols and challenges to the creation of a cross-disciplinary journal - Gould, Thomas H. P. (My University, 2013)
In 2006, The Online Journal of Rural Research & Policy (OJRRP) was launched. The publication is an example of the ability of academia to create narrowly defined scholarly journals aimed at a small, targeted readership, while relying on a meager budget. This paper discusses the factors that fostered the creation of hundreds of online-only journals, as well as provides a case study of the creation of OJRRP and the long-term implications of online cross-discipline publications. Covered areas include the sponsor, editorial board, editorial staff, software, link rot, code, promotional activities, tracking and supporting usage, and, perhaps most important, long-term sustainability. The OJRRP experience is presented, along with lessons learned in each area.
Keywords: Online Journal of Rural Research and Policy; Scholarly journals; Born-online; Cross-disciplinary; Editorial boards; Academic ranking